2017
DOI: 10.1007/s00432-017-2446-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and end-of-life care in patients who have died after allogeneic stem cell transplantation

Abstract: The present investigation indicates that the somatic, psychic and spiritual end-of-life-care after allogeneic stem cell transplantation could be optimised. A significant problem for the transplantation team seems to be the realisation of necessity to switch the curative concept into a palliative ambition. Requirements are a subsequent prospectively conducted investigation and an intensification of cooperation between transplant and palliative care teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Importantly, we have identified many characteristics associated with high quality end-of-life care, including documented goals of care discussion and/or advanced care planning (96%); no chemotherapy in the last 14 days of life (93%); a palliative care consultation after relapse (32%); and hospice enrollment (40%) with a median hospice length of stay of 9 days. Our results compare favorably with aforementioned findings on end-of-life care in older AML patients in which only 23% patients enrolled in hospice (13), and almost 19% patients received chemotherapy in the last 14 days of life (14), and with reports on palliative care provision for these patients at the end-of-life (2123). We do note, however, that our hospitalization/ICU admission rates at the end-of-life remains high at 84% and 33% respectively, similar to 89% and 36% respectively from a previous study (13).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, we have identified many characteristics associated with high quality end-of-life care, including documented goals of care discussion and/or advanced care planning (96%); no chemotherapy in the last 14 days of life (93%); a palliative care consultation after relapse (32%); and hospice enrollment (40%) with a median hospice length of stay of 9 days. Our results compare favorably with aforementioned findings on end-of-life care in older AML patients in which only 23% patients enrolled in hospice (13), and almost 19% patients received chemotherapy in the last 14 days of life (14), and with reports on palliative care provision for these patients at the end-of-life (2123). We do note, however, that our hospitalization/ICU admission rates at the end-of-life remains high at 84% and 33% respectively, similar to 89% and 36% respectively from a previous study (13).…”
Section: Discussionsupporting
confidence: 89%
“…We demonstrate here a high rate of primary palliative care delivery by transplant/leukemia physicians and a high percentage of patients with quality end-of-life care indicators, while the impact of subspecialty palliative care service in this patient population remains to be determined. Considering these patients’ poor prognosis and high symptom burden (22,23), early involvement of subspecialty palliative care service and ongoing collaboration with transplant/leukemia physicians may warrant prospective investigation.…”
Section: Discussionmentioning
confidence: 99%
“…predictor of worse physical and mental health status. Distress was significantly lower than healthy population values, and clinically meaningful: 73 (42.7%) subjects reported high levels of symptoms distress (>15), with a mean number of prevalent symptoms ranging across time from 12 (SD ± 3) to 14 (SD ± 4) symptoms (mean number of symptoms across the cohort: 8 to 10) Busemann 2017 [ 29 ], Germany Retrospective chart review 123 patients who died after allo-SCT Somatic, psychic, and Spiritual needs • About 50% of patients did not live more than 5 months. Two-thirds died within 14 months after SCT.…”
Section: Introductionmentioning
confidence: 99%
“…Rationales for this EOL pattern of care have been proposed, including the unpredictable pattern of clinical decline in patients with hematologic malignancies, clinicians' bias toward offering all possible treatments for these patients, and the small but finite possibility of cure for select patients [17]. Studies have similarly demonstrated that adults undergoing allogeneic HCT for hematologic malignancies use high levels of healthcare resources at EOL [18][19][20][21][22]. However, despite the exceedingly high risk of mortality in AL/MDS patients who relapse after allogeneic HCT, little data exist specifically examining the intensity of healthcare utilization broadly and at the EOL in this patient population, with the few existing studies reporting qualitative or limited data on small patient samples [23,24].…”
Section: Introductionmentioning
confidence: 99%